Heat gains in buildings ‐ Limit conditions for calculating energy consumption - Monstvilas, Edmundas; Banionis, Karolis; Stankevičius, Vytautas; Karbauskaitė, Jūratė; Bliūdžius, Raimondas (Journal of Civil Engineering and Management, 2010)
The results of analysis presented in the paper are related to the certification of energy performance in buildings using calculation methods, when the real energy consumption of the building is not analyzed. Energy consumption for cooling is not examined. Heat transmission losses could be less than the sum of the heat gains of a building if building thermal insulation is sufficient. Currently, the whole amount of heat gains is included into calculation without the evaluation of time parameters. No limit conditions are specified in order to define surplus heat flows and the amount of heat flows so that energy performance of building is calculated. Thus, difference between heat gains and heat flows of a building could be negative. In the paper the basic formation schemes of heat gain access and accumulation are presented due to the presence of people and the bright period of the day. The most adverse circumstances are analyzed for the composition of the proposed schemes. The composition of estimating heat gains is the same for all categories of buildings. Calculation equations have been composed for the estimation of heat gains according to the basic formation schemes. The average monthly parameters of the heating season are used for calculation. The analysis of calculation has been done for the different categories of buildings in order to compare the results of building energy consumption when limit conditions for heat gains are estimated and vice versa. The analysis of different calculation methods of energy consumption has showed that limit conditions for heat gains are important to evaluate the calculation methodology of energy performance for building certification needs. It is important that the calculation methodology of energy performance for building certification would be universal for all EU member states. The presented limit conditions of the heat gains of a building could be used for improving calculation methods of energy consumption in the building certification process. First Published Online: 10 Feb 2011